Thai Consonants Pronunciation of Lua Speakers, Nan Province - Intajamornrak, Chommanad (Journal of Humanities and Social Sciences Review, 2021)
This paper aimed to analyze and compare the Thai consonants pronunciation of the speakers of four Lua dialects in Nan Province which were 1) Ban Sakad Klang Lua Mal, 2) Ban Kwet Lua Mal, 3) Ban Ta Luang Lua Mal, and 4) Ban Huay Lom Lua Pray. The wordlist comprised of Thai consonants occurring in initial, cluster and final position for a total of 41 words. The informants were 20 Lua speakers (five for each language). They were asked to pronounce each test word five times randomly in the sentence frame “say….again”. Total number of test tokens for acoustical analysis was 4,100. The data were recorded directly onto a computer. The results showed that the initial consonants /f/ /s/ and /r/ are wrongly pronounced as [phw] [ch] and [l] respectively. The consonant clusters, both in Consonant + /r/; /kr//khr//pr//phr/ /tr/ and Consonant + /l/; /kl/ /khl/ /pl/ /phl/, were also wrongly pronounced. Only the consonant clusters which were Consonant + /w/; /kw/ /khw/ were all correctly pronounced, as same as the final consonants that the Lua speakers could pronounce all Thai final consonants. It could say that the pronunciation of Thai consonants and tones by Lua speakers was influenced by their mother tongue which was the Lua language. The Lua dialects, which were more different to Thai sound system, were highly interfered than those dialects, which had similar sound system to Thai.